PMF proteins mediate mitochondrial fusion in Arabidopsis - Ryan P. Kenneally; Yu Tang; Wesley J. Bobst; Rui Tong Khor; Lily Garibyan; Neha R. Jag; Yangnan Gu (Proceedings of the National Academy of Sciences, 2026)
Mitochondrial dynamics—continuous fission and fusion—are hallmarks of these organelles and essential for mitochondrial function across eukaryotes. While fission is relatively well understood in plants, the mechanism of fusion remains incompletely defined. In animals and fungi, dynamin-related proteins are emerging fusion factors, but their plant homologs do not localize to mitochondria, suggesting plants rely on a distinct fusion mechanism. Here, we identify PMF1 (Promoter of Mitochondrial Fusion 1) and its paralog PMF2 as plant-specific outer mitochondrial membrane proteins that promote mitochondrial fusion. PMF abundance directly correlates with fusion capacity: overexpression markedly enlarges mitochondria and increases fusion rates, producing megamitochondria, whereas pmf1 pmf2 mutants show reduced mitochondrial volume and severe fusion defects under hypoxic stress. We further show that PMF1’s cytoplasmic, intrinsically disordered N terminus undergoes liquid–liquid phase separation, a property necessary and sufficient to promote mitochondria fusion in vivo. These results reveal PMF-mediated protein condensation as a kingdom-specific mechanism regulating mitochondrial dynamics in plant cells.